PERAN GREENPEACE DALAM REVOLUSI ENERGI FILIPINA The Role of Greenpeace in Philippine Energy Revolution - Rizqi Arindiah Sri Kusuma A (HI 16 UMY 141, 2016)
*141 This paper aims to describe how a Non Government Organization can become an actor in decision making process, using Greenpeace Philippines as one of environment NGO. Greenpeace Philippines bring and introduce Energy Revolution to stop climate change and safe the environment. As a developing country, Philippines has grown fast and their energy depend on the fossil fuel, especially coal. The coal is the single threat for climate. Greenpeace Philippines do campaign to educate people and push the government for fair and legallybinding energy law. nd push